Designing Visual Identity for UMKM Trigel Bakehouse - Mey Dhea Dewi Fajar Lisanti; Pratama Bayu Widagdo (Gorga : Jurnal Seni Rupa, 2025)
Culinary UMKM have great potential in the Indonesian economy, but many of them still lack a strong visual identity to build a professional brand image. Trigel Bakehouse, a home-based bakery established by three women in Semarang, faces similar challenges. This research aims to design the visual identity of Trigel Bakehouse using Robin Landa's Graphic Design Process, which consists of five stages: Orientation, Analysis and Strategy, Conceptual Design, Design Development, and Implementation. Thru this approach, a visual identity system was designed that reflects brand values such as warmth, family, and the quality of homemade products. Design elements include the logo, typography, colors, and supporting media such as packaging, social media, and merchandise, all arranged in a minimalist and elegant style. The results of the design process at the Orientation stage, gathered thru interviews and observations, to explore the background, brand values, and business character. At the Analysis and Strategy stage, the visual condition of the brand, target market, and competitors were analyzed to formulate relevant design strategies. The Conceptual Design phase generates creative ideas thru mindmaps, color selection, typography, and logo development that reflect the values of warmth, family, and professionalism. The Design Development phase finalizes the logo, patterns, and logo versatility for consistent use across various media. The Implementation phase applies the visual identity to business cards, menus, social media, merchandise, signage, pamphlets, packaging, and uniforms, ensuring consistent application across all media. This design resulted in a consistent visual identity that strengthened the brand image, increased brand awareness, and enhanced Trigel Bakehouse's competitiveness in the local culinary market.